자기주도 학습 전략이 국어 · 영어 학업성취도에 미치는 영향에 관한 메타분석 - 남가영; 맹은경 (언어와 정보 사회, 2018)
The purpose of this study is to examine an overall picture of the effect of self-directed learning strategy(SDLS) on Korean and English learning by providing reliable common effect sizes. This study also aims to analyze moderating variables(subjects/grade levels) on Korean and English academic achievement. Through a comprehensive search, a total of 47 primary studies were selected and 16 samples based on correlations and 31 samples based on means were analyzed to compute the effect sizes using Comprehensive Meta-Analysis software. The major findings are as follows: 1) SDLS is effective to enhance Korean and English academic achievement. An overall weak to medium correlation and an medium to large effect size are shown. 2) The relationship between Korean and SDLS is not different from that of English. 3) The overall relationship between academic achievement and SDLS is the same regardless of grade levels. However, the effect size of SDLS on Korean is higher in middle schools than that in high schools whereas the effect sizes of SDLS on English shows no moderating effect between school levels. More studies related to Korean, English as well as various grade levels should be conducted to analyze the moderating effect size more accurately.
Keywords: 자기주도 학습 전략; 자기조절학습; 국어 및 영어 학업성취도; 메타(초)인지 전략; 메타분석; self-directed learning strategy; self-regulated learning; Korean and English academic achievement; meta-cognitive strategy; meta-analysis